2021
DOI: 10.3892/ijmm.2021.4879
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA LINC01006 exhibits oncogenic properties in cervical cancer by functioning as a molecular sponge for microRNA‑28‑5p and increasing PAK2 expression

Abstract: As previously reported, long intergenic non-protein-coding RNA 1006 (LINc01006) plays crucial roles in prostate, pancreatic and gastric cancers. However, whether it plays important roles in cervical cancer remains unclear. The present study thus aimed to determine the precise role of LINc01006 in cervical cancer and elucidate its regulatory mechanisms. The expression of LINc01006 in cervical cancer was examined by reverse transcription-quantitative polymerase chain reaction. Cell proliferation assay, flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… 29 LINC01006 is upregulated in cervical cancer and indicated a poor prognosis. 16 miR-3199 could serve as a mighty biomarker for recurrence prediction among patients with hepatocellular carcinoma 30 and contribute towards survival prediction of lung adenocarcinoma. 31 In this study, we detected LINC01006 and miR-3199 in colon cancer tissues and cells at an elevated and a reduced expression level, respectively, via RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 LINC01006 is upregulated in cervical cancer and indicated a poor prognosis. 16 miR-3199 could serve as a mighty biomarker for recurrence prediction among patients with hepatocellular carcinoma 30 and contribute towards survival prediction of lung adenocarcinoma. 31 In this study, we detected LINC01006 and miR-3199 in colon cancer tissues and cells at an elevated and a reduced expression level, respectively, via RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs exert their functions by multiple mechanisms, in which functioning as decoys and scaffolds of miRNAs, so-called miRNA “sponges”, was the main way. 32 LINC01006 has been proved as miR-28-5p sponge in cervical cancer, 16 miR-129-2-3p sponge in lung Adenocarcinoma. 33 By using bioinformatics analysis and experimental verification, we found LINC01006 was a sponge of miR-3199 in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was identified that miR-28-5p directly targeted CDKN2B-AS1. The localization of miR-28-5p in the cytoplasm and its interaction with lncRNAs have been studied in numerous cancers including CRC (23,24). Moreover, the results revealed that the expression of miR-28-5p was negatively correlated with the expression of CDKN2B-AS1 in CRC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…P21-activated kinase 2 (PAK2), a Rac1/Cdc42 activated signaling effector, belongs to the PAK family of serine/threonine kinases (20). The antiapoptotic effect of PAK2 has been demonstrated in multiple cancer studies (21)(22)(23). Recently, PAK2 has been reported to exert cardioprotective role by improving ER function through the inositol-requiring enzyme 1 (IRE1)/X-box binding protein 1 (XBP1)-dependent pathway (24).…”
Section: Introductionmentioning
confidence: 99%